Least mastered competencies in biology: Basis for instructional intervention - Jack Torno Delos Santos; Roselyn Lim; Danilo V. Jr Rogayan (JPBI (Jurnal Pendidikan Biologi Indonesia), 2021)
Teaching the students of today’s generation has been a perennial challenge for the teachers, particularly in providing these students the core competencies to be more globally competitive and functionality literate in science and in biological disciplines in particular. The purpose of this study was to determine the least mastered competencies of 10 graders in different biology competencies they learned from grade 7 to grade 10. The researchers used a quantitative descriptive cross-sectional study utilizing a self-made survey questionnaire. The respondents were 122 of 10 graders of three state-owned secondary schools in Zambales, Philippines. The findings showed that the biology competencies for seven and eight graders were the least mastered by graders. There were also significant differences of students’ least mastered competencies by school and sex. There were also significant correlations among the least mastered competencies in biology. The study recommends that science teachers may consider employing inquiry-based and hands-on learning activities to further enhance the proficiency of students in biology and decrease students’ difficulties.